Longer Prehospitalization and Preintubation Periods in Intubated Non-survivors and ECMO Patients With COVID-19: A Systematic Review and Meta-Analysis - Funakoshi, Kenji; Morita, Takayoshi; Kumanogoh, Atsushi (Frontiers in Medicine, 2021)
Purpose: There is no clear consensus on the clinical course of critical COVID-19 patients. We examined the clinical course among intubated survivors, nonsurvivors, and extracorporeal membrane oxygenation (ECMO) patients to reveal the standard clinical course and the difference among critical COVID-19 patients. Methods: In this systematic review and meta-analysis, we searched PubMed, Web of Science, and Scopus for original studies published until August 13, 2020, including case accumulation and clinical course reporting. Pregnant patients and children were excluded. We followed PRISMA guidelines and registered them with PROSPERO (CRD42021235534). Results: Of 5486 studies identified, 62 met the selection criteria, and 1950 cases were included in this meta-analysis. The times from intubation to extubation and death were 12.62 days (95% confidence interval 10.34–14.90 days) and 10.60 days (8.38–12.81 days), respectively, and the ECMO duration was 14.34 days (8.34–20.34 days). The time from symptom onset to hospitalization (prehospitalization period) of intubated survivors, nonsurvivors, and ECMO patients was 5.69 (4.10–7.29 days), 6.27 (4.17–8.37 days), and 7.22 days (6.13–8.31 days), and that from symptom onset to intubation (preintubation period) was 8.97 (6.94–11.00 days), 10.01 (6.36–13.66 days), and 10.80 days (8.46–13.14 days), respectively. Sensitivity analysis showed that the time from intubation to extubation and death was longer in the US and Europe than in East Asia. Conclusion: For COVID-19, we hypothesize that prehospitalization and preintubation periods are longer in intubated nonsurvivors and ECMO patients than in intubated survivors. These periods may serve as a predictor of disease severity or death and support therapeutic strategy determination.